THE MATERIALS TO SPECIES COMPOSITION OF TESTACEOUS MITES (ACARI, ORIBATIDAE) OF IRGANAY ARID HOLLOW OF THE INTERNAL MOUNTAIN DAGESTAN - G. M. Abdurahmanov; A. Z. Davudova (Юг России: экология, развитие, 2014)
As a result of the reseach and the laboratory processing of the material at the territory of Irganay hollow of Internal mountain Dagestan there hare been registered about 101 species of testaceous mites (acari, Oribatidae), that belong to 66 genera. 9 species have been indicated in Dagestan fauna for the first time, and 14 species hauen,t determined at au yet.. In addition, two species were found (Oribatella abdurachmanovi [11], Oribatula (Zigoribatula) caspica [18]), described as new to science.